Determination of Preventive Maintenance Electrocardiogram Using the Analytical Hierarchy Process (AHP) Method - Handayani Handayani; Sri Arttini Dwi Prasetyowati (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Abstract Electrocardiogram is a medium-tech diagnostic electromedical device that is widely available in healthcare facilities. Electrocardiogram maintenance is very important to maintain the performance and accuracy of reliable results for medical diagnosis. Suboptimal Electrocardiogram maintenance can be caused by various factors, including user negligence, improper use, component damage, and lack of preventive maintenance. Therefore, this study aims to determine the selection of preventive maintenance strategies on electrocardiograms that are right on target in order to minimize damage, maintain the reliability of the electrocardiogram, and provide optimal maintenance. The research method used is the Analytical Hierarchy Process (AHP). The results obtained from the AHP method are the Warehouse Backup criteria have the highest priority weight of 0.184 and the alternative with the highest priority weight is Periodic Maintenance of 0.3744, then followed by Repair Maintenance (Schedule Overhaul) of 0.3184 and the last is Condition Based Maintenance of 0.3072. The periodic maintenance strategy has the greatest weight, so it is chosen as the most appropriate strategy to be used as optimal maintenance and is expected to be an effective solution so that it can successfully reduce damage and maintain the reliability of the Electrocardiogram. Keywords: analytical hierarchy process (AHP), maintenance, maintenance strategy